Application Of Methods For Playing Wall-Based Cancel To Improve Activities And Learning Outcomes Student Students Social Science World Material II - Sugio, Kusno (Metafora: Education, Social Sciences and Humanities Journal, 2019)
The study of the application of pictorial word guessing methods to improve the activity and learning outcomes of class IX A social studies subjects in World War 2 material and consequently in Sugio 1 Public Middle School 2018/2019 school year aims to apply the method of guessing words to improve learning activeness and results students of class IX A on social studies subjects especially material for World War 2 and consequently even semester 2018/2019 as many as 24 students. The method of data collection is done through tests, observations, documents and interviews. The data analysis technique was carried out by analyzing the average score of the students' performance in the teaching and learning activities. Determine student learning outcomes. Calculates the percentage of students who have successfully taken the test. Data collection. This class action is carried out in 2 cycles consisting of the planning, implementation stages. Observation and reflection. In cycle 1 to cycle 2 there is an increase in the results of completeness of learning outcomes of students.Â Keywords : Picture word guessing games, Active students in learning